2014
DOI: 10.1002/cld.323
|View full text |Cite
|
Sign up to set email alerts
|

Stent placement in perihilar cholangiocarcinoma

Abstract: http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)2046-2484/homepage/3-4-reading-queen.htm a video presentation of this article http://onlinelibrary.wiley.com/journal/10.1002/(ISSN)2046-2484/homepage/3-4-interview-adler.htm the interview with the author https://www.wileyhealthlearning.com/Activity/2621766/Activity.aspx

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 24 publications
0
2
0
Order By: Relevance
“…Among the complications of stent therapy includes clogging with stones or obstruction with tumor ingrowth or overgrowth [48]. Despite complications, stenting can improve the quality of life in patients with cholangiocarcinoma (Table 1) [42].…”
Section: Endoscopymentioning
confidence: 99%
“…Among the complications of stent therapy includes clogging with stones or obstruction with tumor ingrowth or overgrowth [48]. Despite complications, stenting can improve the quality of life in patients with cholangiocarcinoma (Table 1) [42].…”
Section: Endoscopymentioning
confidence: 99%
“…In the context of unresectable disease, it may be performed percutaneously or endoscopically (with stenting) depending on institutional experience, anatomical and biological factors, and the presence of cholangitis [ 80 ]. Tumour progression can lead to decreased stent patency requiring stent replacement [ 81 ]. Several studies have shown prolonged stent patency with the use of local therapies, including intraluminal brachytherapy and radiofrequency ablation (both with and without chemotherapy), leading to improved outcomes in patients [ 82 , 83 , 84 , 85 ].…”
Section: Systemic Therapy For Unresectable Advanced or Metastatic Bil...mentioning
confidence: 99%